2014
DOI: 10.1108/tg-10-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

Jordan’s e-Government at the crossroads

Abstract: Purpose – The purpose of this paper is to assess the maturity level of the Jordanian electronic Government (e-Government) program from the citizen’s perspective. This assessment aims to help in determining whether the Jordanian e-Government strategy, set back in 2002, has achieved its main objectives which are delivering services to people across society, irrespective of location, economic status, education or ICT ability; improving the ICT readiness and infrastructure; and developing new servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…The EGDI is a composite measure of three important dimensions of E-Gov, namely: provision of online services, telecommunication connectivity and human capacity (explained in [5]). Notably, Jordanians do not lack the technical competencies to use the internet and information technology applications whereAl-Soud et al [9], indicated that 75.7 percent are able to use internet services andAbu-Shanab et al [10], reported that spread of internet 85 percent in north of Jordan. The results of UN surveys in Table 2 affirmed that, the average of human capital index always good where (0.72) was the lowest average in 2014 and this above the world and region averages.…”
Section: E-government Rank and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The EGDI is a composite measure of three important dimensions of E-Gov, namely: provision of online services, telecommunication connectivity and human capacity (explained in [5]). Notably, Jordanians do not lack the technical competencies to use the internet and information technology applications whereAl-Soud et al [9], indicated that 75.7 percent are able to use internet services andAbu-Shanab et al [10], reported that spread of internet 85 percent in north of Jordan. The results of UN surveys in Table 2 affirmed that, the average of human capital index always good where (0.72) was the lowest average in 2014 and this above the world and region averages.…”
Section: E-government Rank and Problem Statementmentioning
confidence: 99%
“…The online service index shows that Jordan average above the world average but still lower than regional average (see [1]). The E-Gov program in Jordan still lagging behind in utilizing information and communication technologies for delivering government e-services [11].The comprehensive study that cover whole Jordan byAl-Soud et al [9], revealed that more than 60 per cent out of (4294) respondents (citizens) do not actually know about E-Gov services and the worst result 70 percent of who used the E-Gov services found it not useful. Another study in northern Jordan found that usage of E-Gov 36 percent of the sample.Therefore, this study aims to quest the reasons led participants to gauge E-Gov in Jordan as such.…”
Section: E-government Rank and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of countries, in both developed and developing nations, have started e-government programs that aim to provide public services online, improve government procedures and, most importantly, provide improved services for citizens (Laudon and Traver, 2009;Molla and Licker, 2009;Leonard, 2012;Anas et al 2014). In regards to the e-government in Jordan, in particular, some researches related to e-government have been published.…”
Section: Factors Influencing E-government Adoption In Jordanmentioning
confidence: 99%
“…In regards to the e-government in Jordan, in particular, some researches related to e-government have been published. For example, Anas et al (2014) have discussed the maturity level of the Jordanian electronic government program from the citizen's perspective and found that citizen's interest in e-government services is declining due to awareness problem. Al Hujran et al (2013) have studied the factors influencing citizen adoption of e-government in Jordan and found that ease of use, perceived usefulness, satisfaction, trust, responsiveness, reliability and information technology as important factors.…”
Section: Factors Influencing E-government Adoption In Jordanmentioning
confidence: 99%